2004
DOI: 10.1093/humrep/deh273
|View full text |Cite
|
Sign up to set email alerts
|

Defining poor ovarian response during IVF cycles, in women aged <40 years, and its relationship with treatment outcome

Abstract: Definitions of poor response should include the degree of ovarian stimulation used. A low oocyte number is only detrimental if the cumulative dose is >3000 IU FSH. Cancellation at >/=300 IU FSH/day is associated with a significantly worse prognosis and could define poor response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(26 citation statements)
references
References 31 publications
0
26
0
Order By: Relevance
“…16 Exogenous FSH is administrated to women undergoing IVF and variable ovarian responses have been reported, ranging from high response to the minimal dose of FSH which causes ovarian hyper stimulation syndrome (OHSS), to poor response even with higher doses of FSH which leads to low retrieved mature oocytes. 17 The poor responders may need to repeat stimulation cycles with higher financial burden. According to the present results which indicated that SNP of the core promoter region at position -29 of the FSHR gene may influence sensitivity of the FSHR to FSH in vivo, it may be suggested that women with A/A genotype at position -29 will show poor ovarian response, and so will require higher doses of exogenous FSH for ovulation induction during IVF process.…”
Section: Discussionmentioning
confidence: 99%
“…16 Exogenous FSH is administrated to women undergoing IVF and variable ovarian responses have been reported, ranging from high response to the minimal dose of FSH which causes ovarian hyper stimulation syndrome (OHSS), to poor response even with higher doses of FSH which leads to low retrieved mature oocytes. 17 The poor responders may need to repeat stimulation cycles with higher financial burden. According to the present results which indicated that SNP of the core promoter region at position -29 of the FSHR gene may influence sensitivity of the FSHR to FSH in vivo, it may be suggested that women with A/A genotype at position -29 will show poor ovarian response, and so will require higher doses of exogenous FSH for ovulation induction during IVF process.…”
Section: Discussionmentioning
confidence: 99%
“…The cut-off levels for the number of follicles or oocytes that define poor response vary widely from study to study. Some authors feel that the definition of poor response should also include the degree of ovarian stimulation used and that a low oocyte number is detrimental only when high total dose of follicle stimulating hormone (FSH) has been administered [139]. Various endocrine and ultrasonographic markers and dynamic tests to assess ovarian reserve have been evaluated.…”
Section: Poor Ovarian Responsementioning
confidence: 99%
“…In addition to a quantitative reduction of their oocyte cohorts, poor ovarian responder patients (PORs) present a high risk of implantation failure that may suggest a compromised oocyte quality [2]. …”
Section: Introductionmentioning
confidence: 99%